Poliploidia e variações reprodutivas em Bombacoideae (Malvaceae): distribuição geográfica, filogeografia e tamanho do genoma - Marinho, Rafaela Cabral (2018)
The emergence of apomixis is related to climatic changes that would influence the rapid expansion of this mode of asexual reproduction, currently found in the Cerrado, with significant frequency. Most apomictic species are polyploid and are commonly associated with the presence of polyembryonic seeds. Therefore, in this study the presence of polyembryony implies the development of extra embryos formed from apomitic processes. These phenomena can influence the genetic structure leading to ecological and evolutionary consequences and should be better understood for tropical plants. The species Eriotheca pubescens (subfamily Bombacoideae, Malvaceae) has a wide distribution in this biome and presents a reproductive and cytological mosaic. The geographical distribution of these patterns is not clearly defined, so the first chapter of this study was aimed increasing the knowledge of the reproductive and cytological mosaics in a geographic context in the Stellate Trichoma Complex (E. pubescens + E. estevesiae). For this, we evaluated the presence of polyembryony associated with the asexual reproduction mode and we used morphometric measures of the stomata to estimate ploidy. In this study, we found that stomata measurements worked only partly as a ploidy estimator on a regional scale. Polyembryony was found in half of the populations, all of which are hexaploid and have relatively large stomata. The monoembryonic populations of Eriotheca estevesiae, considered diploid, presented the smallest stomata, while stomata of intermediate size were observed in a tetraploid population (CRI), already described in an earlier study. However, an unexpected variation in stomata size did not allow a clear relationship with ploidy in five monoembryonic populations. In the second chapter, we used sequences from regions of plastid DNA to understand the distribution of the reproductive and cytological systems of the Stellate Trichome Complex in a phylogeographic context, comparing distribution patterns with other Cerrado species and still verifying the genetic similarity between the species that form the complex. It was possible to verify that there is a bigger structuring in the polyembryonic/hexaploid populations and that the phylogeographic patterns are similar to some already described for other species and associated to the paleoclimatic changes in distribution of the Cerrado vegetation. The study showed that the two species studied share a predominant 4 haplotype and a population of E. estevesiae presents a unique haplotype. In the third chapter a compilation of genome size and chromosome number data was presented in species of the Malvatheca clade, together with the presentation of new genome size data for Bombacoideae species and determination of the number of chromosomes of a newly described species of genus Eriotheca. In this study we found more robust data for the subfamily Malvoideae than in Bombacoideae and the average size of the genome is significantly larger in Bombacoideae. A strong correlation between genome size and chromosome number was found only in Eriotheca species with incomplete polyploid series. Comparing the genome size (1Cx) of the main genera that form the clade Pachira, it was possible to verify that the Eriotheca genus has a smaller size of average genome than Pachira indicating a different genomic origin between the genera that have been included in a clade. The chromosome number obtained for E. estevesiae was 2n=2x=92 chromosomes, and this result was important because it corroborated the data of morphometric measures of stomata described in the first chapter and also completes the polyploid series proposed for the complex formed by E. pubescens and E. estevesiae.